PENGARUH SUHU TERHADAP STABILITAS BERBAGAI PRODUK TABLET NIFEDIPIN - Luawo,, Elda F; citraningtyas, Gayatri; Kojong, Novel (UNIVERSITAS SAM RATULANGI, 2012)
Drug storage at heat air condition, high humidity room, and exposed with light lead todrug degradation. Temperature changes is one of external factor cause unstability ofpharmaceutical product.The purpose of this research is to examine the effect of temperature onnifedipin stability. The method using in this research is factorial Complete Random design.There are two factors. Factor A is temperature(40oC, 50 oC, and 60 oC) and factor B are period(60, 120 and 180 minutes). There are three samples in this research research. Analysis ofnifedipin content using Spectrophotometer UV-Vis. Obtained data were analyzed using spss ver.20. The differences between variable were statistical analyzed. The results shows that sample Aat temperature 60 oC, after 180 minutes treatment decrease to 86,47%, Sample B 86,43%, andsample C 85,66%, respectively. Temperature significantly effect on the stability of nifedipin(p<0,05).Keywords: temperature, stability, Nifedipin